Determinants of Switching Intention: Empirical Evidence from Sharia Bank Mergers in Indonesia - Qurniawati, Rina Sari; Nurohman, Yulfan Arif; Fatharani, Aulia (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
This study examines the factors that affect customers switching intention after threeÂ state-owned IndonesianÂ banks merge. The risk of losing customers in mergers and acquisitions (M&A) is very high because during the integration phase, management often focuses on internal issues, leaving aside important customer-related tasks. Therefore, a deeper understanding of the concept of M&A in the disciplines of marketing and consumer behavior is clearly needed for the benefit of academic knowledge and marketing practice. A total of one hundred and fifty respondents are selected using the quantitative method as sources of data collection. The questionnaires are distributed using a purposive sampling method in Surakarta, Indonesia. The software used for analysis is SEM-PLS. The results of this study state that inconvenience and religious motivation influence customer switching intentions. However, attitude and availability of suitable banks as a moderating variable did not influence customer switching intentions.